Bridging the transatlantic divide in privacy - Paula Kift (Internet Policy Review, 2013)
In the context of the US National Security Agency surveillance scandal, the transatlantic privacy divide has come back to the fore. In the United States, the right to privacy is primarily understood as a right to physical privacy, thus the protection from unwarranted government searches and seizures. In Germany on the other hand, it is also understood as a right to spiritual privacy, thus the right of citizens to develop into autonomous moral agents. The following article will discuss the different constitutional assumptions that underlie American and German attitudes towards privacy, namely privacy as an aspect of liberty or as an aspect of dignity. As data flows defy jurisdictional boundaries, however, policymakers across the Atlantic are faced with a conundrum: how can German and American privacy cultures be reconciled?